Inhibitory effect of vanillin on the virulence factors and biofilm formation of Hafnia alvei. (March 2019) - Li, Tingting; He, Binbin; Mei, Yongchao; Wang, Dangfeng; Sun, Xiaojia; Li, Jianrong
Abstract: The aim of this study was to evaluate the effect of vanillin as a QS inhibitor at sub-minimal inhibitory concentrations (sub-MICs) against fish spoilage by Hafnia alvei . Biofilm formation, swimming and swarming activity, and production of acyl-homoserine lactones (AHLs) were measured. In addition, analysis of quorum sensing (QS)-related genes by real-time quantitative PCR (RT-qPCR) and molecular docking was performed to better understand the inhibitory mechanism of vanillin. The results indicated that sub-MICs of vanillin induced remarkable reduction in violacein production (59.0%) and biofilm formation (68.5%) along with decreased swimming ability, and reduced expression levels of halI and halR. Moreover, the results of molecular docking revealed that vanillin and C6 -HSL could form 2 hydrogen bonds with the LuxR protein (HalR), suggesting a potential competitive tendency between them. Thus, our study provides a basic inhibition mechanism of vanillin and suggests its prospective application as a QS inhibitor. Highlights: C6 -HSL positively modulated the spoilage potential of H.alvei. Quorum sensing phenotype was inhibited effectively by vanillin. HalI and halR gene transcription level was down-regulated by vanillin. The potential application of vanillin may be expanded in food processing.